Association of Aspirin Use with In-Hospital Mortality in Patients with Radiation-Associated Acute Pneumonitis: Insights from the National Inpatient Sample Database - Akash Sharma; Shalini; Sowntappan Balasubramanian; Hamza Yousaf; Ankit Agrawal; Vrinda Vyas (Healthcare, 2026)
Introduction: This study investigates the relationship between long-term aspirin use and mortality in patients experiencing acute radiation-induced pulmonary complications. Methods: We conducted a secondary analysis from the National Inpatient Sample from 2016 to 2020. Our cohort comprised patients diagnosed with acute pneumonitis secondary to chest radiation. We adhered strictly to the STROBE checklist, extracting various patient characteristics for analysis. Categorical variables were compared using Pearson’s chi-square test, while continuous variables were assessed using Student’s two-sample t test. To assess the relationship, we employed multivariable-adjusted logistic regression, presenting results as odds ratios (ORs) with 95% confidence intervals (CIs). Results: The study included a total of 6064 hospitalizations: 5204 hospitalizations were in the not-taking-aspirin group (NAG), while 860 were in the aspirin group (AG). The mean age of the NAG cohort was 68.67 ± 12.31 years (mean ± SD), while for the AG it was 72.64 ± 8.87 (mean ± SD) years. Our multivariable analysis revealed that aspirin use is associated with 29% lower odds mortality (aOR = 0.71, 95% CI = 0.54–0.94, p = 0.02) than the NAG. Patients with heart failure (aOR = 0.34, 95% CI = 0.18–0.64, p < 0.001) showed the most significant mortality benefits. No mortality advantages of aspirin were observed in patients with coronary artery disease, percutaneous coronary intervention, or coronary artery bypass grafting. Conclusions: Aspirin use in patients with acute chest radiation is associated with decreased odds of mortality, particularly in those with a history of congestive heart failure.